Functional and spatial proteomics profiling reveals intra- and intercellular signaling crosstalk in colorectal cancer - Christina Plattner; Giorgia Lamberti; Peter Blattmann; Alexander Kirchmair; Dietmar Rieder; Zuzana Loncova; Gregor Sturm; Stefan Scheidl; Marieke Ijsselsteijn; Georgios Fotakis; Asma Noureen; Rebecca Lisandrelli; et al. (iScience, 2023)
Summary: Precision oncology approaches for patients with colorectal cancer (CRC) continue to lag behind other solid cancers. Functional precision oncology—a strategy that is based on perturbing primary tumor cells from cancer patients—could provide a road forward to personalize treatment. We extend this paradigm to measuring proteome activity landscapes by acquiring quantitative phosphoproteomic data from patient-derived organoids (PDOs). We show that kinase inhibitors induce inhibitor- and patient-specific off-target effects and pathway crosstalk. Reconstruction of the kinase networks revealed that the signaling rewiring is modestly affected by mutations. We show non-genetic heterogeneity of the PDOs and upregulation of stemness and differentiation genes by kinase inhibitors. Using imaging mass-cytometry-based profiling of the primary tumors, we characterize the tumor microenvironment (TME) and determine spatial heterocellular crosstalk and tumor-immune cell interactions. Collectively, we provide a framework for inferring tumor cell intrinsic signaling and external signaling from the TME to inform precision (immuno-) oncology in CRC.